Capgras Syndrome in Schizophrenia: A Case Report of Delusional Misidentification and Its Clinical Implications - Duaa Fatima; Ateeq-Ur-Rehman Sheikh; Sadaf Ghulam Jelani; Palvisha Sajid; Imtiaz Ahmad Dogar (BJPsych Open)
Aims: Capgras syndrome (CS) is a rare delusional misidentification syndrome characterized by the belief that a close relative has been replaced by an identical impostor. It is commonly associated with schizophrenia and other psychiatric disorders.